1982
DOI: 10.1111/j.1469-8137.1982.tb03397.x
|View full text |Cite
|
Sign up to set email alerts
|

INTERACTION Between A VESICULAR–ARBUSCULAR MYCORRHIZAL FUNGUS AND STREPTOMYCES CINNAMOMEOUS AND THEIR EFFECTS ON FINGER MILLET

Abstract: SUMMARYGrowth and phosphorus nutrition of finger millet (Eleusine coracana) on a sterile, phosphorusdeficient soil was improved by inoculation with either the vesicular-arbuscular mycorrhizal fungus Glomus fasciculatus or with the streptomycete Streptomyces dnnamomeous. These micro-organisms interacted antagonistically when added simultaneously or with one 2 weeks after the other: Streptomyces reduced spore production and development of infection by Glomus, while Glomus reduced the multiplication of Streptomyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(11 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Such an effect of biocontrol agents on vesicular arbuscular mycorrhiza has been shown before (Calvet et al, 1989;Krishna et al, 1982; see also Linderman and Paulitz, 1990). Interestingly, T. harzianum or T. harzianum combined with G. mosseae induced accumulation of large quantities of glyceollin similarly as the pathogen R. solani.…”
Section: Discussionsupporting
confidence: 54%
“…Such an effect of biocontrol agents on vesicular arbuscular mycorrhiza has been shown before (Calvet et al, 1989;Krishna et al, 1982; see also Linderman and Paulitz, 1990). Interestingly, T. harzianum or T. harzianum combined with G. mosseae induced accumulation of large quantities of glyceollin similarly as the pathogen R. solani.…”
Section: Discussionsupporting
confidence: 54%
“…However, information is limited for rhizosphere microorganisms or mechanisms that suppress mycorrhizal formation. Streptomyces cinnamomeous has been found to reduce mycorrhizal colonization of roots (Krishna et al, 1982). Several fluorescent pseudomonads can produce antifungal compounds (Gurusiddaiah et al, 1986) and Dhillion (1992) reported that inoculation of rice plants with fluorescent Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, shifts in the microbial community in the soil amended with Streptomyces were maintained until the end of experiment. Bacteria are well-known to alter fungal development such as germination rate, foraging behaviour, hyphal branching, growth, survival, reproduction, exudate composition and antibacterial metabolites production (Krishna et al, 1982;Barea et al, 2005;de Boer et al, 2005;Kesba and Al-Sayed, 2006;Franco-Correa et al, 2010). Previous studies have demonstrated that Streptomyces sp.…”
Section: Effect Of Pratylenchus Penetrans and Streptomyces Sp Ach 50mentioning
confidence: 99%